2021
DOI: 10.1177/20494637211014544
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of botulinum toxin type-A for intractable chronic migraine patients with no pain-free time

Abstract: Aim: This is a retrospective report of the efficacy of botulinum toxin-A, Botox® (Allergan), in intractable chronic migraine patients non-responsive to previous pharmacological management and with largely no pain-free time, including those with new onset daily persistent headache. Methods: Thirty-three patients, all with severe Headache Impact Test (HIT)-6 scores at baseline, received 3-monthly injections of Botox® as per Phase III REsearch Evaluating Migraine Prophylaxis Therapy (PRE-EMPT) protocol over a max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Although limited randomized, double-blind, placebo-controlled studies exist, our study aligns with previous research suggesting the efficacy of Botulinum toxin A in migraine prevention. In one study, 30% of patients in both botulinum toxin A treatment groups experienced a 50% or greater reduction in migraine frequency in the third month relative to baseline, compared to 25% in the placebo group (P = 0.921) (17). Our findings also align with a study evaluating headache days, migraine days, acute pain medication ingestion days, and HIT-6 score reductions in 172 patients treated with OnabotulinumtoxinA 195 U over two years.…”
Section: Discussionsupporting
confidence: 82%
“…Although limited randomized, double-blind, placebo-controlled studies exist, our study aligns with previous research suggesting the efficacy of Botulinum toxin A in migraine prevention. In one study, 30% of patients in both botulinum toxin A treatment groups experienced a 50% or greater reduction in migraine frequency in the third month relative to baseline, compared to 25% in the placebo group (P = 0.921) (17). Our findings also align with a study evaluating headache days, migraine days, acute pain medication ingestion days, and HIT-6 score reductions in 172 patients treated with OnabotulinumtoxinA 195 U over two years.…”
Section: Discussionsupporting
confidence: 82%
“…A case series of 16 patients with NDPH treated with onabotulinumtoxinA injections reported that eight (50%) had an improvement in headache frequency after six months (56). In another study of onabotulinumtoxinA, which included nine patients with NDPH, two patients had an improvement of Headache Impact Test-6 score (57). Unfortunately, a previous open-label clinical trial of onabotulinumtoxinA for NDPH was terminated due to difficulty with enrolment (58).…”
Section: Injectable and Neuromodulatory Treatmentsmentioning
confidence: 99%
“…Patients with continual headaches were excluded from phase II to phase III study, presumably due to concern of reduced response to primary end points, limiting generalisability and data for these patients 7 8. Within our cohort, a significant difference was seen in the clinical efficacy of CGRP mAbs in patients who reported no headache-free days at baseline, and with the number of previously trialled preventative medications, highlighting the need for further treatment options in this cohort.…”
Section: Discussionmentioning
confidence: 97%